Abiotic and biotic factors influencing western United States coniferous forests - Lalande, Bradley, author; Stewart, Jane, advisor; Stromberger, Mary, committee member; Tinkham, Wade, committee member; Trivedi, Pankaj, committee member (Colorado State University. Libraries, 2019)
In the next decade, climate models suggest that global temperatures will continue to rise. In the western United States, increases in temperatures and changes in precipitation patterns will escalate the risk of drought conditions. These potentially warmer, drier conditions could induce physiological changes within trees, subsequently increasing stress on coniferous forests that are adapted to cool, wet environments. The abiotic stress accompanied by drought conditions can predispose susceptible hosts to biotic stress of insect and disease populations. In particular, high elevation subalpine fir (Abies lasiocarpa) have encountered higher than average mortality rates throughout the western United States in association with abiotic and biotic agents. Chapter 2 of this thesis investigated the potential drivers of subalpine fir mortality and determined how climatic factors and site and stand characteristics influenced the presence of mortality and biotic agents. The objectives were to identify factors driving subalpine fir mortality in Colorado and included 1) determine abiotic and biotic factors that directly and indirectly affect subalpine fir mortality, 2) determine factors associated with the presence of D. confusus or Armillaria spp., and 3) determine if climate variables were correlated to subalpine fir mortality or the presence of D. confusus and Armillaria spp. I hypothesized that sites with a higher density (i.e. basal area, trees per hectare, or canopy closure) would experience greater mortality due to decreased growth rates from competition and that D. confusus or Armillaria spp. prevalence would be a function of tree stress (i.e. increased density), elevation, slope, and departures from normal precipitation (i.e. drought), and minimum and maximum temperatures. Stand health monitoring plots found that the most relevant factors to subalpine fir mortality are the presence of D. confusus (p = 0.003) and the percent subalpine fir on plot (p = <0.0001). I identified that stand density (p = 0.0038), elevation (p = 0.0581), and Armillaria spp. (p = 0.0006) were the greatest influences on the presence of D. confusus, while the largest influences on the presence of Armillaria spp. are warmer maximum summer temperatures (p = 0.0136) and the presence of D. confusus (p = 0.0289). Results indicated that increased subalpine fir mortality was attributed to high stand density as a predisposing factor, warming temperatures as an inciting factor, and bark beetles (Dryocoetes confusus) and root disease (Armillaria spp.) as contributing factors. The combination of predisposing, inciting, and contributing factors suggests that subalpine mortality can be defined as subalpine fir decline. Management strategies used to reduce the impact of subalpine fir decline will need to address ways to improve stand health, while decreasing populations of both, D. confusus and Armillaria spp. In regards to Armillaria, the inability to successfully manage the disease using current techniques highlights the need to find novel management strategies to minimize its impacts. Since this disease is a root pathogen, soil microbes likely influence its growth and survival. Utilizing soil microbial communities as biocontrols may assist in management of Armillaria. Field sampling within the Priest River Experimental Forest in northern Idaho provided the opportunity to observe how soil microbial communities are associated with two species of Armillaria, A. solidipes (primary pathogen) and A. altimontana (weak pathogen). My research objective for Chapter 3 was to identify the soil fungal communities associated with tree health status (healthy, moderate and dead) and each Armillaria species, A. solidipes and A. altimontana, both of which have differing ecological behaviors (virulent pathogen and non-pathogen, respectively) on western white pine. I hypothesized that soil microbial communities associated with virulent A. solidipes and non-pathogenic A. altimontana would differ in fungal richness and diversity with the latter having a greater richness and diversity due to its beneficial qualities to tree health. While richness and diversity is likely to shift among tree health with a greater diversity and richness for soils associated with healthy trees due to root exudate production near the rhizosphere. Soil samples were collected alongside western white pine (Pinus monticola), while Armillaria rhizomorphs were excavated near the roots. The most abundant fungal taxon was Mortierella spp., which functions as saprophyte decomposing dead and down wood. No significant differences in fungal diversity or richness were found in soils associated with Armillaria species, but, although not significant, there where slight differences between soils associated with moderate and dead trees with a greater diversity and richness in soils with dead trees (p = 0.18). Additionally, soil pH was significantly influenced by soil carbon, nitrogen, and organic matter, while moisture significantly influenced soil carbon, nitrogen, and organic matter, acting as indicators to overall health in the stand. Although not significantly different, more Hypocreaceae (Trichoderma), a known biocontrol for root pathogens, were found within soils associated with A. altimontana and healthy trees. More research is needed to solidify differences, yet these factors give insight into potential beneficial aspects of soil fungal communities in association with Armillaria species and tree health. Changing climates regimes outside of 30-year averages cause increased stress to forests. This stress may predispose trees to a greater abundance biotic agents such as bark beetles and secondary pathogens, such as Armillaria root disease specifically in association with subalpine fir in Colorado. Understanding the role that soil fungal communities play in association to Armillaria root disease and tree health may assist in forest management practices to increase the health of high elevation forests.
Keywords: climate; fungi; subalpine fir mortality; soil microbiome; Dryocoetes confusus; Armillaria root disease